ROLE OF RND-EFFLUX PUMP IN LEVOFLOXACIN RESISTANCE AMONG ACINETOBACTER BAUMANNII - A., Ali M.; Mahmood, S.S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
In this study out of 130 different clinical specimens, 70 Acinetobacter baumannii were collected from hospitalized patients. Then; all the isolates were characterized using biochemical tests and confirmed by using the Vitek II compact system. All isolates of Acinetobacter baumannii were subjected to the disc diffusion method to determine it’s a susceptibility to 8 types of antibiotic disc, and the result showed these bacteria were resistant to Cefepime, Imipenem, trimethoprim, Piperacillin, tetracycline, Amikacin, ampicillin-sulbactam and levofloxacin. According to bacterial susceptibility test, all isolated were showed highly resistance to Trimethoprim (88.57%) and the lower resistance to tetracycline (47.14%). Minimum inhibitory concentration was determined only for levofloxacin resistant isolates of Acinetobacter baumannii using the broth dilution method. MIC shows these bacteria were resistant to levofloxacin in concentration ranging between 32µg/100µl to 128µg/100µl. The relation between adeIK and levofloxacin resistance was calculated by determining gene expression using real-time PCR. The result showed the mean value of adeI and adeK before exposing bacteria to levofloxacin was 2.3 and 0.42 respectively while the mean value of adeI and adeK after exposing bacteria to levofloxacin was 3.15 and 3.29 respectively. This study indicates that adeI has a non-significant role (p-value=0.11) in providing resistance to levofloxacin, while adeK plays a significant role (p-value= 0.008) in providing resistance to levofloxacin.